Family Kinship in Community-Based Tourism Businesses in Homestay Entrepreneurs Organization in Raja Ampat - Kurnia Fahmy Ilmawan; Andreas Yogi Prasetyo (Tourism Department, State Polytechnic of Banyuwangi, 2023)
The success and sustainability of tourism depends on the local community as the social unit that supports tourism. Community-based tourism initiatives offer solutions to place communities as the main actors in tourism development. In the implementation of tourism business development, communities in Raja Ampat Regency utilize social capital as a tribal, kinship and family unit in developing their businesses. Family members as part of the kinship unit often play a role in running economic businesses and often take part in making important decisions that affect the course of tourism businesses. This paper aims to determine the form and relationship of kinship among members of the Raja Ampat indigenous business and livelihood association, as well as provide a case example of an organization whose decision-making is based on the kinship of its members. Based on the results of the analysis, it is known that family kinship as social capital has an important role in running tourism businesses, and homestay tourism businesses in Raja Ampat are formed because they have an extensive family kinship network. This is closely related to the concept of kinship adopted by the Biak tribe. This complexity also affects the running of the organization and decision-making in the organization of homestay entrepreneurs in Raja Ampat, such as the election of the chairman who comes from the clan with the largest number of members and other decision-making processes.